Geochemistry, Re–Os isotopes and highly siderophile element abundances in the Eastern Pontide peridotites (NE Turkey): Multiple episodes of melt extraction–depletion, melt–rock interaction and fertilization of the Rheic Ocean mantle - Dokuz A.; Uysal I.; Dilek Y.; Karsli O.; Meisel T.; Kandemir R. (My University, 2014)
We report on the structure, geochemistry, Re–Os isotopes and relative abundances of highly siderophile elements (HSEs) of the Paleozoic peridotite–basalt occurrences in the Eastern Pontide belt of northeastern Turkey. These peridotites and the associated basaltic rocks are the remnants of the Rheic oceanic lithosphere, incorporated into the Eurasian continental margin during the Variscan (Hercynian) orogeny. The peridotites display a complex record of multiple magmatic, metasomatic and metamorphic events in different tectonic settings during the evolution of the Rheic upper mantle. The Beyçam harzburgite (BH) contains low Al2O3 (0.51–1.88 anhydrous wt.%) and high MgO (41.35–42.34 wt.%) contents, and its bulk-rock trace element compositions are less than 10% of the primitive upper mantle (PUM) values. The platinum, Pd and Re contents of the Beyçam harzburgite are highly depleted, whereas its Os, Ir, and Ru contents are slightly enriched relative to the PUM values. Its Pd and Re contents that are higher than those of the fertile Pulur lherzolite (PL) to the south and the absence of an isochronous relationship between its 187Os/188Os and 187Re/188Os show that the trace element distribution and the isotope ratios of the Beyçam harzburgite were significantly modified after the first melt-extraction episode. The first melt extraction occurred beneath the Rheic mid-ocean ridge spreading center, whereas the second melt extraction occurred in a mantle wedge above a Rheic subduction zone. The primary magmatic phases of the Pulur lherzolite show the geochemical characteristics typical for fertile lherzolite, formed in the early stages of oceanic lithosphere generation subsequent to the continental break up. The Pulur lherzolite also contains a secondary magmatic phase in the form of networks of clinopyroxene veins and channels, which are interpreted as an evidence for solid state melt–rock reactions between the lherzolite and a percolating basaltic melt above a subduction zone. This clinopyroxene addition resulted in the formation of variable concentrations of Al2O3 (2.47–4.33 wt.%) and MgO (29.76–40.10 wt.%) in the lherzolite. The rhenium, Pd and Pt concentrations of the Pulur lherzolite are depleted relative to the PUM values, whereas the Os, Ir and Ru concentrations are in the range of the PUM values as commonly observed in peridotites with a melt depletion history. The high suprachondritic 187Os/188Os is, however, inconsistent with a simple melt depletion history, and can be explained by the addition of radiogenic Os-bearing sulfide phases into the lherzolite as a result of melt–rock reactions. Basaltic rocks with an island arc tholeiitic composition from the Beyçam area represent the partial melting product of the moderately depleted Beyçam harzburgite and the basaltic parental melt from which the clinopyroxene precipitated. The covariation between the 187Re/188Os and 187Os/188Os of these basaltic rocks defines an isochron age of 377 ± 8 Ma (late Devonian). The combined structural, geochemical and isotope data indicate a prolonged history of multiple episodes of melt extraction–depletion, and melt–rock interaction and fertilization of the mantle lithosphere of the Rheic Ocean.
Keywords: highly siderophile elements; Re–Os isotopes; melt extraction; melt–rock interaction and peridotite; refertilization; Eastern Pontide belt (NE Turkey)